Faktor-faktor yang Mempengaruhi Kesempatan Kerja pada Sektor Pertanian di Provinsi Kalimantan Selatan - Wafa Wafa; Lina Suherty (PPJP Universitas Lambung Mangkurat, 2023)
The purpose of this study is to determine what factors influence and are the most dominant in employment opportunities in the agricultural sector in South Kalimantan. This study uses time series data from 2005-2019, the data used are obtained from the Central Statistics Agency of South Kalimantan Province. The analytical method used is multiple regression analysis which is calculated using the Eviews application.The results obtained from this study are the variables of the agricultural sector GRDP, labor force, Farmer Exchange Rates (NTP) and The Provincial Minimum Wage (UMP) have a significant simultaneous effect on job opportunities in South Kalimantan Province. The most dominant factor in influencing job opportunities in South Kalimantan Province is the labor force.